miR-139-5p Inhibits the Epithelial-Mesenchymal Transition and Enhances the Chemotherapeutic Sensitivity of Colorectal Cancer Cells by Downregulating BCL2 - Li, Qingguo (Sci Rep, 2016)
MicroRNAs (miRNAs) are important regulators involved in various cancers, including colorectal cancer (CRC). The functions and mechanisms of the miRNAs involved in CRC progress and metastasis are largely unknown. In this study, miRNA microarray analysis was performed to screen crucial miRNAs involved in CRC progress, and miR-139-5p was chosen for further study. The functional roles of miR-139-5p in colon cancer were demonstrated by CCK-8 proliferation assay, cell invasion and migration, cell apoptosis and in a KO mouse study. miR-139-5p expression was significantly decreased in cancer tissues compared to normal tissues. The miR-139-5p expression level was associated with tumour stage (P < 0.01). Function studies revealed that miR-139-5p was significantly correlated with the metastasis potential and drug resistance of colon cancer cells by affecting the epithelial-mesenchymal transition (EMT). Then, we identified BCL2 as a direct target of miR-139-5p cells in vitro. The patient samples and KO mice model showed that BCL2 expression was inversely correlated with the expression of miR-139-5p. In conclusion, we found that miR-139-5p targeted the BCL2 pathway to reduce tumour metastasis and drug sensitivity in CRC. This axis provided insight into the mechanism underlying miRNA regulation of CRC metastasis and a novel therapeutic target for CRC therapy.